2021
DOI: 10.1093/femsyr/foab019
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-induced internalization of the S. cerevisiae galactose permease Gal2 is dependent on phosphorylation and ubiquitination of its aminoterminal cytoplasmic tail

Abstract: The hexose permease Gal2 of Saccharomyces cerevisiae is expressed only in the presence of its physiological substrate galactose. Glucose tightly represses the GAL2 gene and also induces the clearance of the transporter from the plasma membrane by ubiquitination and subsequent degradation in the vacuole. Although many factors involved in this process, especially those responsible for the upstream signaling, have been elucidated, the mechanisms by which Gal2 is specifically targeted by the ubiquitination machine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 52 publications
1
23
0
Order By: Relevance
“… 5 pUCP1 CEN6/ARS4 , URA3 , Ampicillin marker, HXT7p -1-392 , CYC1t Ref. 28 pUCP1 GAL2 N376Y/M435I -GFP pUCP1 GAL2 N376 Y/M435I -GFP under control of HXT7p -1-392 and CYC1t This study pUCP1 GAL2 6 SA/N376Y/M435I -GFP pUCP1 GAL2 6SA/N376Y/M435I -GFP under control of HXT7p -1-392 and CYC1t This study …”
Section: Methodsmentioning
confidence: 85%
See 2 more Smart Citations
“… 5 pUCP1 CEN6/ARS4 , URA3 , Ampicillin marker, HXT7p -1-392 , CYC1t Ref. 28 pUCP1 GAL2 N376Y/M435I -GFP pUCP1 GAL2 N376 Y/M435I -GFP under control of HXT7p -1-392 and CYC1t This study pUCP1 GAL2 6 SA/N376Y/M435I -GFP pUCP1 GAL2 6SA/N376Y/M435I -GFP under control of HXT7p -1-392 and CYC1t This study …”
Section: Methodsmentioning
confidence: 85%
“…This process is induced by phosphorylation and ubiquitination of the N-terminal cytoplasmic tail and can be abolished by mutating six serine residues at positions 32, 35, 39, 48, 53 and 55 to alanine. The resulting Gal2 6SA is stable at the plasma membrane even in the presence of glucose 28 . Therefore, we combined the 6SA N-terminal tail with the N376Y/M435I double mutation.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Since our results suggested that the ubiquitinylation of heterologous sugar permeases impair their successful expression in S. cerevisiae, and since this post-translational modification that triggers the endocytosis of the plasma membrane transporters depends on the activity of -arrestins that function as adaptors for the E3 ubiquitin ligase encoded by the essential gene RSP5 [50,51], we tested if deleting -arrestins involved in sugar transporter endocytosis could be another strategy to improve the functional expression of the cloned transporters in S. cerevisiae. Although this yeast has 14 known -arrestins, we focused in two -arrestins known to be involved in sugar transporter endocytosis: ROD1 (also known as ART4 for arrestin-related trafficking adaptors) which has been shown to mediate the ubiquitinylation and endocytosis of the high-affinity HXT6 and HXT4 glucose transporters [52][53][54], the low-affinity HXT1 and HXT3 glucose permeases [55], as well as the GAL2 galactose permease [56]; and its paralog ROG3 (also known as ART7) that has been shown to be implicated in the ubiquitinylation and endocytosis of the low-affinity HXT1 and HXT3 glucose permeases [54,55].…”
Section: Resultsmentioning
confidence: 99%
“…While deletion of ROD1 or both -arrestins in our hxt-null strain had no effect on the absence of growth of the strains expressing the two XUT1 permeases, deletion of ROG3 had a positive effect with both permeases during growth on glucose, but during growth on xylose only the SaXUT1-expressing strain DLG-K1ΔR3 had its growth enhanced (Figure 5). This more complex situation might reflect the fact that most -arrestins have overlapping functions when promoting the ubiquitinylation of the permeases by the RSP5 ubiquitin ligase, and many transporters are regulated by two or even up to four -arrestins, reflecting the diverse signaling pathways that mediate transporter ubiquitinylation and endocytosis triggered by changing environmental conditions [41,50,51,[54][55][56]. Nevertheless, our results highlight the involvement of the ROG3 -arrestin in down-regulation of the heterologous SpXUT1 and SaXUT1 permeases expressed in S. cerevisiae in the presence of glucose, while a more complex situation is evident when xylose is the carbon source for growth.…”
Section: Discussionmentioning
confidence: 99%